Design and Construction of a Liquefied Petroleum Gas (LPG) Leak Detection System Based on the Internet of Things - Ohoiwutun, Johanis Soinngil; Tamtelahitu, Trientje Marlein; Siwalette, Reynaldi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The use of LPG as an energy source in the community carries the risk of leakage that can endanger the safety of life and the environment. This research aims to design and build an LPG gas leak detection system based on the Internet of Things (IoT) using MQ-2 sensors and NodeMCU ESP8266. The methods used are Research and Development (R&D) with the hardware design stage, programming using the Arduino IDE, and integration with the Blynk application for monitoring and notifications. The MQ-2 sensor is used to read the gas level, while a buzzer and virtual LEDs are used as warning indicators. The test results showed that the system was able to detect gas levels above the 400 ppm threshold, providing real-time alerts through buzzers and app notifications with a quick response. Gas level data is also displayed in the form of a graph for easy monitoring. The system works stably as long as it is connected to a Wi-Fi network. Thus, this system has been proven to be effective, accurate, and can increase awareness of the potential danger of LPG leaks.